Antibiotics use in patients with COVID-19 in a national hospital in Lima, Perú - Carrasco-Lozano, Luis Enrique (2023)
Objective: To determine the frequency of antibiotic use in patients with COVID-19 in a national hospital in Lima, Peru, as well as their laboratory characteristics and outcomes. Findings: 274 patients were included, with a prevalence of general and early antibiotic therapy of 45.62% and 28.1% respectively, with a mortality of 37.59%. General antibiotic therapy was associated with leukocytosis, left shift, and increased PCR. Early antibiotic therapy was associated with leukocytosis and left shift. The frequency of admission to the ICU was higher in patients with early antibiotic therapy. There was no association between general or early antibiotic therapy with mortality. Conclusions: The frequency of antibiotic use in patients with COVID-19 is high, mainly associated with leukocytosis and left shift; and does not decrease mortality.